Molecular Dynamics Simulation of Zener Pinning by Differently Shaped and Oriented Particles - Li, Yi; Zhou, Jian; Li, Runjie; Zhang, Qingyu (Frontiers in Materials, 2021)
Zener pinning between a curved Cu grain boundary (GB) and a differently shaped and oriented Ag particle has been simulated via molecular dynamics. The computed magnitudes of the maximum pinning force agreed with theoretical predictions only when the force was small. As the force increased, discrepancy became obvious. Through carefully inspecting structures of the Cu-Ag interfaces, detailed interaction processes and variation of the Cu GB during the interaction, the discrepancy is found to correlate with GB faceting, which very likely reduce the maximum pinning force and facilitate boundary passage. GB anisotropy and/or interface natures are also found to slightly contribute to the discrepancy. These findings suggest that the assumption of an isotropic GB with constant energy utilized in previous theoretical works for deriving the maximum pinning force might be inappropriate and an accurate maximum pinning force could not be predicted without knowing the effects of GB evolution together with detailed properties of both GBs and interfaces.